Seni Pertunjukan Ritual Dalam Upacara Labuhan Di Parangkusuma - Y. Murdiyati (Mudra Jurnal Seni Budaya, 2009)
The study aims to understand, to analyses, and to descript the meaning of the Bedaya Sangga Buwana Dance in the ritual ceremony and to add or to increase the meaning of the dance in the ritual ceremony in Parangkusuma. The existence of ritual ceremony in Parangkusuma has aim role thank to the God, and ask the health. The conclution of the article is: (a) the ceremony and traditional ritual aim to continu and to increase the culture values, (b) the ceremony and the traditional ritual are hoped as the instrument of connection between the nations in the world, and (c) the Bedaya Sangga Buwana Dance is connected with the ritual ceremony.